Study on the Effect of Fertilizers and Hydrogen Peroxide on Soil Property, Growth, Yield and Nutrient Content of Abelmoschus Esculentus (L.) Moench - Selvaananthi A; Beulah Jerlin (Hasanuddin University, 2020)
Effect of the application of individual and combination of vermicompost, NPK along with H2O2 was studied on 10, 20, 30, and 40 days old seedlings of Abelmoschus esculentus. The physio chemical characters of soil with vermicompost showed better result and it has all kinds of nutrient needed for the better growth of the crop. It increases soil fertility, crop production and nutrient content of the plants. Integrated fertilizer application will boost the crop and this is the best way to obtain better results and it will decrease the pollution load on our environment. Application of H2O2 also influences the germination, early plant growth and nutrient content. It act as a growth promoter, but the continuous application and accumulation leads to damages, and the disease resistance against pathogens was decreased during the reproductive stages.